Carbon capture and storage: progress and next steps - International Energy Agency (IEA) (2010)
Since 2008, significant progress has been made to address the high‐level recommendations on carbon capture and storage (CCS) made by the G8 Leaders. CCS has advanced towards commercialization, notably through the commissioning of CCS pilot plants, continued learning from plants already in operation and the development of legal and regulatory frameworks. Several governments have committed to provide over USD 26 billion in funding support for demonstration projects. International collaborative and public outreach activities have increased substantially. The mapping of suitable storage sites is underway in various countries and a guide for CCS‐ready plant has been developed.